2017
DOI: 10.5130/cjlg.v0i19.5451
|View full text |Cite
|
Sign up to set email alerts
|

Citizen participation in urban local government: a case study of Kanaighat Paurashava in Bangladesh

Abstract: Scholars have identified many variables as determinants of citizen participation, but not all of these are relevant to citizen participation in specific cultural and political contexts. This paper seeks to identify the specific factors which work as drivers for citizen participation in Bangladesh through a case study of Kanaighat Paurashava (municipality), an urban local government. It identifies the following variables which strongly affect citizen participation: the role of elected representatives, notably t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Communities, civil societies, and government jointly seek effective ways to engage people in decision-making process to strengthen the civic culture (Denhardt et al 2009). They use participation to increase citizen's sense of responsibility, encourage people to listen to diverse opinions, strengthen the legitimacy of decision-making, and better implement projects (Chowdhury and Aktaruzzaman 2016). In contrast, in developing countries, lack of a democracy, lack of deeply entrenched civil societies, poverty, lack of institutional infrastructure (Denhardt et al 2009), mistrust between people and government, lack of access to information, lack of necessary facilities and expertise, large-scale discrimination, and legal and managerial challenges are the main hurdles to public participation in decision-making processes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Communities, civil societies, and government jointly seek effective ways to engage people in decision-making process to strengthen the civic culture (Denhardt et al 2009). They use participation to increase citizen's sense of responsibility, encourage people to listen to diverse opinions, strengthen the legitimacy of decision-making, and better implement projects (Chowdhury and Aktaruzzaman 2016). In contrast, in developing countries, lack of a democracy, lack of deeply entrenched civil societies, poverty, lack of institutional infrastructure (Denhardt et al 2009), mistrust between people and government, lack of access to information, lack of necessary facilities and expertise, large-scale discrimination, and legal and managerial challenges are the main hurdles to public participation in decision-making processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2009; OECD 2020; Yang and Callahan 2007). In fact, participation, which is the process of building relationships between the people and the government, is used to provide better and effective services to the members of the community (Biocchi 2003; Chowdhury and Aktaruzzaman 2016; Nguyen et al. 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have found that this unequal distribution of reserved seats quota policy could not ensure women members’ effective participation in the Union Parishad (Begum 2012; Panday 2013; Prodip 2015). Other studies have argued that lack of adequate resource distribution among the members in general seats and reserved seats limits women's meaningful participation in the Union Parishad (see, for example, F. D. Chowdhury 2013 and Sogra 2008). Although women members represent bigger electorates than the male members represent, they obtain the same amount of remuneration as the male members (Mukhopadhyay and Meer 2004; Sogra 2008).…”
Section: Quota Provisions In India and Bangladesh: A Comparative Pers...mentioning
confidence: 99%
“…For those who do not carry out reporting, they will be subject to a maximum of 3 months imprisonment and a maximum fine of 25 million rupiahs. The expected participation of the community becomes very weak because the community feels that they do not have a direct responsibility and their participation will have no effect on the decision-making process (Chowdhury & Aktaruzzaman, 2016). Instead, the Directorate General of Immigration could expand the application to gain more public participation.…”
Section: The Practical Aspects Of E-government Development In the Fie...mentioning
confidence: 99%